Non-iterative Determination of Latitude and Longitude from Either Time or Phase Differences - Campbell, Andrew C. (The International Hydrographic Review, 2018)
A method for the determination of latitude and longitude from hyperbolic coordinates is presented in this article. The hyperbolas may be expressed in either time differences or phase differences. The solution may be for two systems of curves having a common master station, or it may be for two independent systems each having its own master station. The new solution is compared to the iterative solution and, like this solution, an initial approximation for position is also required. Unlike the iterative solution, the initial approximation has little effect on the results in the non-iterative method, providing that the approximation is within three miles. More accurate transformations are obtained with less computer time.